PENGARUH PENGGUNAAN RAPORT DIGITAL MADRASAH (RDM) DAN SUPERVISI AKADEMIK KEPALA MADRASAH TERHADAP KUALITAS LAPORAN NILAI SISWA DI SMP-IT AS’ADIYAH DAPOKO KABUPATEN BANTAENG - Mar'ah, Khaeratul; Syamrina; Putra, Sul Pratama; Yaumi, Muhammad; Damopolii, Muljono (Educational Leadership: Jurnal Manajemen Pendidikan, 2025)
This study aims to determine the effect of using the Digital Madrasah Report (RDM) and the academic supervision of the madrasah head on the quality of student score reports at SMP-IT As’adiyah Dapoko, Bantaeng Regency. This research employs a quantitative approach with an associative type of study. Data collection was conducted through closed questionnaires distributed to teachers and analyzed using multiple linear regression. The results of the study indicate that both the use of RDM and the academic supervision of the madrasah head have a positive and significant effect on the quality of student score reports. The use of RDM has proven to improve the efficiency and accuracy of score reporting, while academic supervision by the madrasah head shows a stronger influence in promoting teacher discipline and professionalism. The conclusion of this study affirms that improving the quality of student score reports cannot be achieved solely through digital systems but also requires active academic leadership. The implication of this research highlights the importance of synergy between administrative digitalization and academic guidance in improving the quality of madrasah education.